(untitled) (Brazilian Journal of Radiation Sciences, 2022)
A new approach for the determination of 210Pb by liquid scintillation counting was developed by the LBIOVT. In order to assess the applicability of the technique for internal monitoring of occupationally exposed workers and members of the public, some probable scenarios for the intake of 210Pb were elaborated and evaluated in this work. The methodology developed provides detection limit values suitable for detecting activities corresponding to committed effective doses below 1 mSv in a variety of scenarios. For members of the public, the time interval between the supposed intake and the collection of the sample could be up to 240 days for daily urine collection or up to 130 days for daily faeces collection. In a monitoring program for occupational exposed workers the methodology developed could be used in a monitoring interval twice an year both for daily urine or faeces collection and the detection limits would still be able to detect activities corresponding to a committed effective doses below the recording level. It is concluded that the methodology developed is suitable to be used for monitoring individual members of the public in case of an accidental exposure or to be used in a monitoring program for occupational exposed workers